Use of oral fluralaner (Bravecto) to successfully manage adult‐onset generalised demodicosis in a silver fox (Vulpes vulpes). Issue 3 (30th August 2019) - Burke, Amanda; Kottwitz, Jack; Wang, Chengming; White, Amelia
Abstract : A six‐year‐old spayed female silver fox ( Vulpes vulpes ) presented with bilateral ocular discharge, lethargy, facial alopecia and dermatitis of six months' duration. The fox was immobilised with ketamine (4 mg/kg), dexmedetomidine (0.01 mg/kg) and butorphanol (0.05 mg/kg) intramuscularly for skin cytology, skin scrapings, dermatophyte culture, bloodwork, faecal floatation and skin biopsies. Diagnostics revealed numerous Demodex species mites. Histopathology showed folliculitis, perifolliculitis and furunculosis with mites, identified as Demodex canis using RT‐PCR. The fox received meloxicam (0.2 mg/kg by mouth, three days), cefovecin (8.6 mg/kg subcutaneously, single injection), praziquantel (56.8 mg, subcutaneously, single injection), and fluralaner (250 mg, by mouth, once every 12 weeks, Bravecto). Complete resolution was noted one month after initiating treatment. Thirteen months later the fox remains mite‐free and is receiving fluralaner by mouth every 12 weeks. This case report describes successful management of adult‐onset generalised Demodex species dermatitis in a silver fox using oral fluralaner.